Code-Switching and Code-Mixing among Users of Social Media - Nur Rasyidah Mohd Nordin (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
AbstractThis conceptual paper aims to examine the use and application of code-switching and code-mixing among users of social media based on recent studies in Sociolinguistics. Communication in general has evolved tremendously in the 21st century, as it has made interactions with people all around the world much faster and easier. Social media is an important platform that allows these interactions to take place. Having multiple users from different countries influences the utilization of the first language (mother tongue), code-switching, code-mixing and borrowed words. Social media users have been shown to extensively use code-mixing and code-switching, particularly among speakers in the bilingual or multilingual society. Thus, this conceptual paper will attempt to deliberate on the use of code-switching as well as code-mixing among users of social media; namely people’s preference of social media, types and use of code-switching and code-mixing on social media, and lastly factors which influence the use of code-switching and code-mixing on social media. Keywords: Code switching; Code mixing; Sociolinguistics; Social media